Design of a high performance variable structure position control of ROVs - da Cunha, J.P.V.S.; Costa, R.R.; Liu Hsu (IEEE journal of oceanic engineering, 1995)
An adaptive control scheme for dynamic positioning (DP) of remotely operated underwater vehicles (ROV) is proposed based on a recently developed output feedback variable structure control (VSC) algorithm named VS-MRAC. Only position measurement is required. Precise modeling of the ROV is not needed and unmodeled perturbations can be effectively rejected. A simple method for discretizing the original continuous-time VS-MRAC is proposed based on dead-beat response. Other important practical implementation issues are considered. The performance is evaluated by simulation with a realistic ROV model and by full-scale experimental pool tests with an actual ROV.< >